Use new PLGL-RGD-NGF nerve conduits for promoting peripheral nerve regeneration - Yan Qiongjiao (BioMedical Engineering OnLine, 2012)
Abstract Background Nerve conduits provide a promising strategy for peripheral nerve injury repair. However, the efficiency of nerve conduits to enhance nerve regeneration and functional recovery is often inferior to that of autografts. Nerve conduits require additional factors such as cell adhesion molecules and neurotrophic factors to provide a more conducive microenvironment for nerve regeneration. Methods In the present study, poly{(lactic acid)-co-[(glycolic acid)-alt-(L-lysine)]} (PLGL) was modified by grafting Gly-Arg-Gly-Asp-Gly (RGD peptide) and nerve growth factor (NGF) for fabricating new PLGL-RGD-NGF nerve conduits to promote nerve regeneration and functional recovery. PLGL-RGD-NGF nerve conduits were tested in the rat sciatic nerve transection model. Rat sciatic nerves were cut off to form a 10 mm defect and repaired with the nerve conduits. All of the 32 Wistar rats were randomly divided into 4 groups: group PLGL-RGD-NGF, group PLGL-RGD, group PLGL and group autograft. At 3 months after surgery, the regenerated rat sciatic nerve was evaluated by footprint analysis, electrophysiology, and histologic assessment. Experimental data were processed using the statistical software SPSS 10.0. Results The sciatic function index value of groups PLGL-RGD-NGF and autograft was significantly higher than those of groups PLGL-RGD and PLGL. The nerve conduction velocities of groups PLGL-RGD-NGF and autograft were significantly faster than those of groups PLGL-RGD and PLGL. The regenerated nerves of groups PLGL-RGD-NGF and autograft were more mature than those of groups PLGL-RGD and PLGL. There was no significant difference between groups PLGL-RGD-NGF and autograft. Conclusions PLGL-RGD-NGF nerve conduits are more effective in regenerating nerves than both PLGL-RGD nerve conduits and PLGL nerve conduits. The effect is as good as that of an autograft. This work established the platform for further development of the use of PLGL-RGD-NGF nerve conduits for clinical nerve repair.